Micro-ring devices and circuits - Tobing, Landobasa Yosef Mario A. L. (2010)
A microring resonator is a realization of Fabry-Perot etalon in planar technology. The cavity mode of a microring resonator is normally excited by evanescent coupling from optical waveguides, which are analogous to semi-reflecting mirrors, and with resonance characteristics based on the ring circumference. Microring resonators have been extensively exploited in various active and passive functions, owing to their compact size and highly resonant behavior. Their planar nature allows integration with many resonators in a variety of array geometries, extending the functionalities even further to higher order filter and delay lines, which are important for optical interconnects. For the above reasons, the microring resonator is often thought as a good candidate in integrated optics. This thesis is focused on the theoretical analysis, device design, and experimental demonstration of integrated optical devices derived from coupled microring resonators. The main idea of this research is to exploit inter-cavity interactions in certain multi-resonator configurations for application-specific purposes ranging from box-like filters to optical bistable switches. The proposed devices have been fabricated and experimentally verified using the CMOS-based silicon-on-insulator technology, under ePIXnet platform. Experimental results show excellent agreement with theoretical predictions.